2020
DOI: 10.1111/jdi.13207
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of hypoxanthine and xanthine by obesity in a general population

Abstract: Aims/Introduction: Uric acid is synthesized by oxidation of hypoxanthine and xanthine using a catalyzing enzyme, xanthine oxidoreductase (XOR), which can be a source of reactive oxygen species. Plasma XOR activity is a metabolic biomarker associated with obesity, hyperuricemia, liver dysfunction and insulin resistance. However, it has recently been reported that XOR activity in fat tissue is low in humans, unlike in rodents, and that hypoxanthine is secreted from human fat tissue. Materials and Methods: The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 41 publications
6
25
1
Order By: Relevance
“…Since hypoxanthine is a precursor of xanthine, this association between hypoxanthine and xanthine might be easy to conceive. Significant associations between the plasma levels of hypoxanthine and xanthine, and between the plasma xanthine and XOR activity were also reported by another study conducted in the general population 23 . The plasma XOR activity and xanthine levels, but not the plasma hypoxanthine level, were correlated with the BMI, unlike the results of a previous study 23 .…”
Section: Discussionsupporting
confidence: 69%
“…Since hypoxanthine is a precursor of xanthine, this association between hypoxanthine and xanthine might be easy to conceive. Significant associations between the plasma levels of hypoxanthine and xanthine, and between the plasma xanthine and XOR activity were also reported by another study conducted in the general population 23 . The plasma XOR activity and xanthine levels, but not the plasma hypoxanthine level, were correlated with the BMI, unlike the results of a previous study 23 .…”
Section: Discussionsupporting
confidence: 69%
“…Significant associations between the plasma levels of hypoxanthine and xanthine, and between the plasma xanthine and XOR activity were also reported by another study conducted in the general population [29]. The plasma XOR activity and xanthine levels, but not the plasma hypoxanthine level, were correlated with the BMI, unlike the results of a previous study [29]. Hypoxanthine is a known marker of hypoxia [32,33] and a recent study revealed that the secretion of hypoxanthine from the adipose tissue increased in response to local hypoxia [34].…”
Section: Discussionsupporting
confidence: 71%
“…Since hypoxanthine is a precursor of xanthine, this association between hypoxanthine and xanthine might be easy to conceive. Significant associations between the plasma levels of hypoxanthine and xanthine, and between the plasma xanthine and XOR activity were also reported by another study conducted in the general population [29]. The plasma XOR activity and xanthine levels, but not the plasma hypoxanthine level, were correlated with the BMI, unlike the results of a previous study [29].…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This could possibly be attributable to the reutilization of hypoxanthine through the salvage pathway 20 xanthine might be easy to conceive. Significant associations between the plasma levels of hypoxanthine and xanthine, and between the plasma xanthine and XOR activity were also reported by another study conducted in the general population 23 . The plasma XOR activity and xanthine levels, but not the plasma hypoxanthine level, were correlated with the BMI, unlike the results of a previous study 23 .…”
Section: Discussionsupporting
confidence: 69%